Comprehensive survey of Early to Middle Triassic Gondwanan floras reveals under-representation of plant–arthropod interactions - Turner, Holly-Anne; McLoughlin, Stephen; Mays, Chris (Frontiers in Ecology and Evolution, 2024)
Plants and arthropods are primary drivers of terrestrial ecosystem function. Trace fossils of plant–arthropod interactions (PAIs) provide a unique window into assessing terrestrial ecosystem states through geological time and evaluating changes in herbivorous arthropod feeding guilds in the wake of global biotic crises. The end-Permian event (EPE; c. 252 Ma) resulted in the loss of keystone plant species from humid tropical and high-latitude ecosystems and the extinction of several major insect groups. The subsequent Early to Middle Triassic evinced diminished terrestrial productivity, punctuated by a series of second-order biotic crises that hindered recovery. Here, we survey records of Gondwanan Early to Middle Triassic floral assemblages for evidence of PAIs as an indication of ecosystem recovery following the EPE. We compiled a comprehensive dataset of fossil plant taxa and PAIs for lower Mesozoic strata of Gondwana, revealing an increase in specific and generic floral diversity from the Early to Middle Triassic. We noted a lack of PAIs reported from many localities with abundant fossil leaves, which might be interpreted to be a consequence of a post-EPE delay in the recovery of arthropod feeding guilds compared to the flora. However, by comparing floral assemblages between regions of Gondwana, our results also partly attribute the absence of PAIs to the relative paucity of palaeoichnological and palaeobotanical studies of this interval. To test for potential under-reporting of PAIs in the Triassic, we present a case study of the well-described Australian Middle Triassic Benolong Flora. In contrast to existing Australian Early to Middle Triassic PAI reports on only three plant specimens, this systematic investigation revealed 44 PAI traces comparable to published examples, hosted by 40 fossil plant fragments (7.77% of fragments assessed; N = 591). Margin-feeding traces constituted the dominant Functional Feeding Group (FFG) identified (23 examples: 3.72% of fragments assessed). Our review highlights several Early and Middle Triassic Gondwanan plant fossil-rich successions and existing collections that require further examination. We predict that investigations of these assemblages will greatly elucidate the relationships between rapidly changing environments during the Early and Middle Triassic and their effects on the plant and arthropod communities in the Southern Hemisphere.